PENGGUNAAN VERBA PADA SURAT KABAR KOMPAS - Nusarini Nusarini (CARAKA, 2016)
This study aims to (1) describe the morphological form of verbs in Kompas newspaper and (2) to describe the syntactic behavior of verbs in Kompas newspaper. The type of this research is descriptive research. Research data in the form of a sentence in which there is a verb, while the data source is Kompas newspaper published in May 2015. Method of providing data used is a listen method to refer to advanced techniques of bebas libat cakap and technical note. The method of data analysis used is the method of agih with advanced techniques of lesap technique, while the method of presentation of the results of data analysis using informal methods because the presentation using ordinary words, not symbols. The results of research are 1. The forms of verbs used in Kompas newspapers include verbs of origin and derived verbs. The derived verb is formed by affixation, reduplication, and compounding. Verb-forming affixes include: meN-, meN-kan, meN-i, memper-kan,memper-i, memper-, di-, di-kan, di-i, diper-kan, ter-, ter-kan,ter-i, ber-, ber-an,Â  dan ke-an. 2. Judging from its syntactic behavior, the verbs found are transitive and nontransitive verbs. Transitive verbs include both transitive and semitransitive verbs, whereas tactransitive verbs include incomplete verbs, compulsory mandatory verbs, and compliant verbs where likes.